Peg + Cat. Pirates ahoy! and other really big problems [videorecording (DVD)] (Peg + Cat, 2014)
Follow the adorable, spirited Peg and her sidekick Cat as they embark on adventures, solve problems together, and learn foundational math concepts and skills. In each episode, Peg and Cat face an issue, a messy funny crisis they must somehow solve without totally freaking out!